The Trade-off Strategy between Financial and Environmental Performance: Assessment of Sustainable Value Added - Munawaroh, Munawaroh; Ghozali, Imam; Fuad, Fuad; Faisal, Faisal (International Journal of Energy Economics and Policy, 2018)
Corporate sustainability issue has considered the most important aspects as it reflects the corporate consideration to environmental, social, and economic dimension. However, using trade-off strategy to assess the relationship between financial performance and environmental performance has not been implemented. The aim of this study was to apply an integrated analysis of trade-off strategy to assess the relationship between financial performance and environmental performance. The method was used Autoregressive to analyze the relationship between Return on Asset (ROA) as financial performance and Eco-Efficiency (EE) as environmental performance. The samples were business sectors non-financial listed in Nikkei225 in the period of 2005 to 2014. The result showed that EE significantly relates to ROA as shown by Granger Causality Test, and their relationship appeared to three sectors of business: Consumer Discretionary, Industrials, and Materials. Eco-Efficentcy significantly related to current financial performance , and the previous year financial performance. The impact of Eco-Efficeincy on the current financial performnace appeared only to sector of business Consumer Discretionary. The investigation applied opportunity cost to assess Sustainable Value Added and to describe the causality between financial performance and environmental performance as well as the trade-off strategy. It is expected that this finding might be considered an environmental management accounting tool to weigh the environmental impacts at different points to life cycle of company. Keywords: Trade off Strategy, Financial Performance, Environmental Performance, Sustainable Value Added, Opportunity Cost, Eco-Efficiency, Autoregressive JEL Classifications: M45, N50, N55